The effect of calcium carbonate content on the zinc quantity-intensity relationship in some soils of Mosul, Irak - Mijbil Mohammed. Aljumaily; Hudhaifa Maan. Al-Hamandi; Mohammed. Ali. Al-Obaidi; Radhwan Rafid AL-Zidan (Ciencia y Tecnología Agropecuaria, 2022)
The quantity-intensity relationship (Q/I) was used to evaluate thermodynamic parameters of zinc in soils under different agricultural management. Ten soil samples were collected from Mosul city to study zinc distribution of calcium carbonate content in these soils. Generally, Q/I relationship of zinc may provide an index for the strength and quantity of effective zinc supply to plants in soils. The Q/I parameters of zincwere studied to quantify zinc release before and after removing carbonates in the studied soils. Results showed that the zinc activity ratio (AReZn) is related to changes with labile zinc (±ΔZn) at equilibrium and increased together with increasing zinc concentrations, intensity (I) ranged between 0.8584 and 0.9972×10-3 mol/L1/2 before removing carbonates and between 0.0909 and 2.7626×10-3 mol/L1/2 after removing carbonates. The ranges of labile Zinc (ZnL) values before and after removing carbonates were between 0.5755-0.7815 and 0.0009-0.0104 cmol/kg, respectively, while the Zinc (PBCZn) before and after removing carbonates fluctuated from 0.5839 to 0.9104 and 0.00112 to 0.00990 cmol/kg(mol/L)−1/2, respectively. That means calcium carbonate increases exchangeable zinc and zinc capacity at equilibrium conditions. The free energy (−ΔF) ranged between -1.001 and -0.979 kJ/mol before removing carbonates and between -1.319 and -0.841 kJ/mol after removing carbonates. Gapon Selectivity Coefficient (kG) ranged between 0.0193835 and 0.027453 and 0.000045 and 0.00450 (mol/L)1/2 before and after removing carbonates, respectively. Therefore, these results may be used as a reference for zinc soil fertilization, whereas thermodynamic parameters values may be used to predict soil ability to supply available zinc.